O ensino médio no Brasil: trajetória e perspectivas de uma organização politécnica entre educação e trabalho - Garrossino, Silvia Regina Barboza [UNESP]; Castro, Rosane Michelli de [UNESP] (My University, 2010)
The objective of this article is to present an abbreviation analysis and interpretation of the path of the medium teaching in Brazil, from where the idea of the relationship emerges between education and work, among theory and practice, and its organization in the molds of the polytechnical education, this last one that had guided the preliminary proposal for the medium teaching presented by Dermeval Saviani, in 1988. In that sense, subjects were approached on education and work. Finally, they were made brief considerations on the theme in the educational context for besides the capital

O objetivo deste artigo é apresentar uma breve análise e interpretação da trajetória do ensino médio no Brasil, de onde emerge a idéia da relação entre educação e trabalho, entre teoria e prática, e sua organização nos moldes do ensino politécnico, este último que havia orientado a proposta preliminar para o ensino médio apresentada por Dermeval Saviani, em 1988. Nesse sentido, foram abordadas questões sobre educação e trabalho. Finalmente, foram feitas breves considerações sobre o tema no contexto educacional para além do capital
Average education in Brazil: trajectory and perspectives of one polytechnical organization between education and work
Keywords: Educação; Ensino médio; Politecnia; educação e trabalho